KOLABORASI METODE DISKUSI DAN TANYA JAWAB UNTUK MENINGKATKAN KEAKTIFAN PESERTA DIDIK PADA PEMBELAJARAN SEJARAH DI MA BAHRUL ULUM KECAMATAN DAYUN - Fikri, Asyrul; Alfiani, Fitri; Faujiyanto, Ahmad; Putri Pertiwi, Ega (Riau Education Journal, 2021)
The ideal learning process is a student-oriented and not boring learning process. The problems identified in history learning are the low active participation of students to be involved in learning activities and the stigma of students stating that history learning tends to be boring. The purpose of this study was to determine the effectiveness of the application of collaborative discussion and question and answer methods in learning compared to the lecture method. This research is a quasi-experimental research. This research was conducted at the Bahlum Ulum Islamic Boarding School, Siak in July 2020. The subjects of this research were female class XI students as experimental class students and female class XII students as control classes. The data collection instrument used was an observation sheet for learning activities. The results of this study indicate that collaborative discussion and question and answer methods are more effective in increasing student participation in the learning process than the lecture method. Â